2019
DOI: 10.1038/s42003-019-0579-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific Mendelian randomization study of genetically predicted insulin and cardiovascular events in the UK Biobank

Abstract: Insulin drives growth and reproduction which trade-off against longevity. Genetically predicted insulin, i.e., insulin proxied by genetic variants, is positively associated with ischemic heart disease, but sex differences are unclear, despite different disease rates and reproductive strategies by sex. We used Mendelian randomization in 392,010 white British from the UK Biobank to assess the sex-specific role of genetically predicted insulin in myocardial infarction (MI) (14,442 cases, 77% men), angina (21,939 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…with masking the type of intervention, long-term compliance, and because of ethical concerns. Alternatively, Mendelian randomization studies are suitable tools to test for causality in humans, and such studies have found hyperinsulinemia to increase the risk of obesity [27,28] and cardiovascular disease [127,128]. A straightforward approach for lowering circulating insulin levels is restricting the exposure of islet ß cells to insulin secretagogues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with masking the type of intervention, long-term compliance, and because of ethical concerns. Alternatively, Mendelian randomization studies are suitable tools to test for causality in humans, and such studies have found hyperinsulinemia to increase the risk of obesity [27,28] and cardiovascular disease [127,128]. A straightforward approach for lowering circulating insulin levels is restricting the exposure of islet ß cells to insulin secretagogues.…”
Section: Discussionmentioning
confidence: 99%
“…Final proof of a causal relationship between hyperinsulinemia and disease risk cannot be obtained by randomized controlled trials, due to problems with masking the type of intervention, long-term compliance, and because of ethical concerns. Alternatively, Mendelian randomization studies are suitable tools to test for causality in humans, and such studies have found hyperinsulinemia to increase the risk of obesity [ 27 , 28 ] and cardiovascular disease [ 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our findings are consistent with well-established evolutionary biology theory, that is reproductive success may be at the expense of longevity, possibly in a sex-specific manner, impling that central drivers of the reproductive axis, as well as androgen production and catabolism, and their environmental cues may be relevant to IHD ( Schooling, 2016 ; Schooling and Ng, 2019 ; Figure 2 ) encompassing the relations tested here ( Figure 1 ). Notably, upregulation of indicators of plentiful living conditions, such as insulin, appear to cause IHD, particularly in men ( Zhao et al, 2019 ), likely via gonadotropin releasing hormone (GnRH) ( Schooling and Ng, 2019 ). Similarly, fatty acids may affect GnRH ( Tran et al, 2016 ; Matsuyama and Kimura, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unregulated fructose metabolism can also raise uric acid concentration, which has been linked to endothelial dysfunction, hypertension, and increased risk of CVD 33 . It is also possible that sugar intake might affect glucagon or insulin which may cause CHD 37,38 . However, we did not find any evidence of these pathways, which need validation using stronger instruments predicting sugar.…”
Section: Discussionmentioning
confidence: 99%